Mechanochemical fabrication of geopolymer composites based on the reinforcement effect of microfibrillated cellulose. Issue 1 (1st January 2023) - Zheng, Yuhang; Wang, Zi; Wan, Zhangmin; Yang, Xuan; Lin, Fengcai; Chen, Yandan; Tang, Lirong; Lin, Guanfeng; Lu, Qilin; Huang, Biao; Lu, Beili
Abstract: In this study, microfibrillated cellulose-reinforced geopolymer organic/inorganic hybrid materials, were prepared via a simple green mechanochemical method. The interaction between microfibrillated nanocellulose and geopolymer was further investigated by molecular dynamics simulation. The study established that mechanical ball milling could effectively promote the microfibrillation of bamboo pulp fibers to form reinforced geopolymer composites with a uniformly distributed cellulose skeleton network. The compressive strength of geopolymer blended with 2% microfibrillated cellulose was shown to be 85.1% higher than that of the pristine geopolymer after 30 days. In addition, the hybrid system was found to maintain excellent thermal stability due to the effective protection of the biomass components by the inorganic matrix. This one-step mechanochemical process provided an efficient approach for preparing geopolymer composites, which offers significant application potential for use in road repairs, high-temperature-resistant materials, and additive manufacturing via 3D printing.